A Discontented Diaspora : Japanese Brazilians and the Meanings of Ethnic Militancy, 1960-1980 - Lesser, Jeff (Book collections on Project MUSE., 2007)
Analyzes the experiences of a generation of Japanese-Brazilians in Sao Paulo during the most authoritarian period of military rule in order to ask questions about ethnicity, the nature of diasporic identity, and Brazilian culture.